PERMASALAHAN KEADILAN DAN KEPASTIAN PERKEMBANGAN HUKUM KETENAGAKERJAAN DI INDONESIA TERHADAP KESEJAHTERAAN HIDUP TENAGA KERJA DAN KEBERLANJUTAN PERUSAHAAN - Tundjung Herning Sitabuana; Rio Kurniawan (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
The conflict between the Corporation and the Workforce is a global phenomenon from time to time that has an impact on changing social conditions. However, the development of law faces obstacles in responding to habits that have been passed down from generation to generation in society. The function of this research is to seek answers in terms of legal certainty and justice regarding the development of legal relations with people's habits in work ethics in the era of modernization and constitutional interpretation of the modernization era that supports sustainable economic development and is in accordance with the identity of the Indonesian nation. This study uses a quantitative juridical analysis method, which is in the form of in-depth research on legal materials and data as usual as normative law. Furthermore, the results of the analysis will be linked to the problems in this study to produce an objective assessment to answer the problems in the study. The results of the study show the steps that must be taken by the Government in a strategic role to make reforms quickly and precisely so that statutory norms can be consistent with the development of society, especially due to developments in work and business ethics. Then, the most ideal and relevant constitutional interpretations for the ratification of the Work Creation 2020 Omnibus Law, namely: Consensualism (current developments), Prudential (costs incurred and the benefits generated), and Futuristic (future conditions) with an emphasis on legal certainty and justice for employers and workers and on the significant socio-economic impacts on general welfare.